Genetic relationships among cultivated and wild bananas from East Kalimantan, Indonesia based on ISSR markers - Widi Sunaryo; Wahida; Suria Darma Idris; Ananda Nuryadi Pratama; Kumrop Ratanasut; Nurhasanah (Society for Indonesian Biodiversity, 2020)
Abstract. Sunaryo W, Wahida, Idris SD, Pratama AN, Ratanasut K, Nurhasanah. 2020. Genetic relationships among cultivated and wild bananas from East Kalimantan, Indonesia based on ISSR markers. Biodiversitas 21: 824-832. East Kalimantan is one of biodiversity centers for banana in Indonesia including wild or cultivated bananas. This biodiversity is long-historical genetically contributed by the existence of wild cultivars, local/indigenous varieties or introduced accessions from other regions in Indonesia. The existence of cultivated bananas has played an important role in the socio-economic significance of the local people. The genetic contribution of wild and local banana from East Kalimantan to the cultivated bananas or vice versa is very interesting to study. This research reported the genetic relationships among wild and cultivated bananas using Inter Simple Sequence Repeat (ISSR) markers. Thirteen wild and cultivated banana samples collected from different districts of East Kalimantan Province were analyzed using 15 primers of ISSR marker. ISSR primers generated 133 loci, of which 132 were polymorphic (98.98 %) with an average of 9.43 loci per primer. The ISSR marker is very effective and powerful to detect and discriminate the polymorphisms among cultivated and wild bananas. This is supported by PIC value which ranged from 0.60 to 0.91 per primer with an average of 0.80 per primer. The marker index (MI) values were ranged from 1.62 to 11.48 per primer. Primer UBC 855 produced the highest MI value which was 11.48 per primer and UBC 848 resulted in the lowest (1.62 per primer). The similarity coefficients ranged from 0.43 to 0.81. The dendrogram constructed based on UPGMA divided the banana cultivars into 4 clusters, in which the first cluster comprised of the AA/AAA/AB genome bananas (Ambon, Kapas, Tembaga, Liar, and Tanduk). The second cluster composed of only Mauli Banana. The third cluster was comprised of six cultivated banana with AAB or ABB genome i.e., Raja, Rutai, Susu, Kepok, Awak, and Talas banana. The last cluster was only Klutuk Banana (BB genome). Wild bananas (Liar and Klutuk) was the ancestor of cultivated bananas since they contributed for A genome (Musa acuminate) and B genome (Musa balbisiana) to generate many triploid and cultivated bananas. Indigenous banana cultivars from Kalimantan, Rutai is closely related to Susu banana, while Talas banana is related to the AAB genome such as Raja, Rutai, Susu or ABB genome such as Awak and Kepok.